(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the educational intervention in nurses’ knowledge related to the physical examination of the child performed in the city of Vitória de Santo Antão, Pernambuco. Quantitative, quasi-experimental, exploratory-descriptive research. The data were recorded in the SPSS software version 20.0, and analyzed using univariate and bivariate descriptive and inferential statistics, which was approved by CAAE nº 29766120.9.0000.9430. Twenty-seven nurses participated in the intervention, most of them female (96.3%), with an average age of 34.85 years and with an average time in the Family Health Strategy of 4.26 years. After the intervention, the participants answered an average of 20.54 questions correctly, characterizing statistically significant differences between the situations. It is evident that the educational intervention provided an increase in nurses’ knowledge about physical examination of children in primary health care, and it is emphasized that training will provide changes in the work process. Thus, the performance of educational intervention activities is essential for the nurse’s care practice.